The Tradition of Reciting Al-Fātiḥah Before Drinking Coffee: A Living Qur’an Study in Martapura, South Kalimantan - Muhammad Haratullisan; Bashori (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2026)
This study provides an in-depth analysis of the tradition of reciting al-Fātiḥah before drinking coffee in Martapura’s majelis taklim as a contemporary expression of the Living Qur’an within Banjar culture. The practice reflects a fusion of sacred text, Hadhrami Sufi devotional ethos, and local hospitality culture through a ritual performance inherited from earlier scholars. Using a qualitative–ethnographic approach, data were collected through participant observation, in-depth interviews with five informants (scholars, organizers, and participants), and textual analysis of Tadzkir al-Nās, and recent Living Qur’an scholarship. The findings show that the ritual takes place when coffee is served during the gathering, accompanied by the recitation of the tawassul, followed by a collective recitation of al-Fātiḥah, even before all participants receive their cups. Genealogically, the practice is rooted in the teachings of Habib Ahmad bin Hasan al-Aṭṭās, who emphasized the blessings and protection associated with al-Fātiḥah, transmitted to Banjar scholars through Hadhrami networks. Spiritually, participants experience tranquility, strengthened intention, and a sense of connection with the masyaikh. Socially, the ritual reinforces solidarity, strengthens communal identity, and creates a distinctive space of religious interaction. The study concludes that this tradition represents a living and performative mode of Qur’anic reception that integrates textual, Sufi, and local cultural dimensions into a unified religious expression serving both spiritual and social functions within Banjar Muslim society.